Penerapan Tax Planning Melalui Zakat Sebagai Pengurang Pajak Penghasilan Terutang (Studi Kasus Pada PR. Semanggimas Agung Kediri) - Nurazzah, Fikriz Ayu; Alfa Niam, Muhammad; Srihastuti, Eni (LPPM Universitas Nias Raya, 2023)
Cigarette Company Semanggimas Agung Kediri is a company engaged in the cigarette industry. The purpose of this research is to find out how the implementation of Tax Planning through zakat is used as a deduction for corporate income tax. The data analysis technique used in this research is descriptive quantitative and the data source used in this research is primary data. From the results of the calculation analysis in this study, it can be concluded that with the implementation of zakat on companies paid to the Amil Zakat Agency and Amil Zakat Institutions that have been established and approved by the government can be used as a deduction from taxable income so as to minimize the company's payable income tax burden. At the Semanggimas Agung Kediri Cigarette Company before the application of zakat, the amount of income tax payable was IDR 2,294,903,402 and after the application of zakat, the company's payable income tax was IDR 2,237,530,835, so that there was a difference in the company's payable income tax before and after the application of zakat, namely in the amount of IDR 57,372,585.